Clarithromycin Suppresses Human Respiratory Syncytial Virus Infection-Induced Streptococcus pneumoniae Adhesion and Cytokine Production in a Pulmonary Epithelial Cell Line. (12th June 2012) - Yokota, Shin-ichi; Okabayashi, Tamaki; Hirakawa, Satoshi; Tsutsumi, Hiroyuki; Himi, Tetsuo; Fujii, Nobuhiro
Abstract : Human respiratory syncytial virus (RSV) sometimes causes acute and severe lower respiratory tract illness in infants and young children. RSV strongly upregulates proinflammatory cytokines and the platelet-activating factor (PAF) receptor, which is a receptor for Streptococcus pneumoniae, in the pulmonary epithelial cell line A549. Clarithromycin (CAM), which is an antimicrobial agent and is also known as an immunomodulator, significantly suppressed RSV-induced production of interleukin-6, interleukin-8, and regulated on activation, normal T-cell expressed and secreted (RANTES). CAM also suppressed RSV-induced PAF receptor expression and adhesion of fluorescein-labeled S. pneumoniae cells to A549 cells. The RSV-induced S. pneumoniae adhesion was thought to be mediated by the host cell's PAF receptor. CAM, which exhibits antimicrobial and immunomodulatory activities, was found in this study to suppress the RSV-induced adhesion of respiratory disease-causing bacteria, S. pneumoniae, to host cells. Thus, CAM might suppress immunological disorders and prevent secondary bacterial infections during RSV infection.